Human erythroid differentiation requires VDAC1-mediated mitochondrial clearance - Moras, Martina (2021)
Erythroblast maturation in mammals is dependent on organelle clearance throughout terminal erythropoiesis. We studied the role of the outer mitochondrial membrane protein voltage-dependent anion channel-1 (VDAC1) in human terminal erythropoiesis. We show that short hairpin (shRNA)-mediated downregulation of VDAC1 accelerates erythroblast maturation. Thereafter, erythroblasts are blocked at the orthochromatic stage, exhibiting a significant decreased level of enucleation, concomitant with an increased cell death. We demonstrate that mitochondria clearance starts at the transition from basophilic to polychromatic erythroblast, and that VDAC1 downregulation induces the mitochondrial retention. In damaged mitochondria from non-erythroid cells, VDAC1 was identified as a target for Parkin-mediated ubiquitination to recruit the phagophore. Here, we showed that VDAC1 is involved in phagophore’s membrane recruitment regulating selective mitophagy of still functional mitochondria from human erythroblasts. These findings demonstrate for the first time a crucial role for VDAC1 in human erythroblast terminal differentiation, regulating mitochondria clearance.